Análise da solicitação de retorno de adultos e idosos usuários de aparelho de amplificação sonora individual no serviço de referência - Sault, Taiane Cristina Leite da Silva (2021)
OBJECTIVE: To analyze the reasons for requesting an appointment to the referral service for adults and elderly hearing aids users, correlating the user's demand and their audiological characteristics with the professional team needed for the assistance. This research is part of the need to identify and classify the demand for feedback from hearing aid users to propose a solution, with the necessary and appropriate professionals for the assistance. METHOD: This is a prospective cross-sectional study. Patients with hearing aids over 18 years of age were included in the survey by phone or attended in person at the hearing health service, affiliated to the Sistema Único de Saúde - SUS - as a Center for Rehabilitation - CER II (hearing and intellectual), to request a return during the month of August 2020. The sample of this study is composed of 177 subjects. RESULTS: Most of the sample consists of women (58.71%) and the elderly, the average age found was 62.84 years. Regarding hearing loss, 67.23% of the subjects have sensorineural hearing loss and 48.59% are of moderate degree. The complaint reported on the day of care was of broken hearing aid: 37,9%, followed by adjustment of hearing aid 26.5%. Of the total number of subjects, 62.1% needed a complete team in care and 37.9% needed a simple team. Regarding the professional conduct adopted, 27.7% required audiological monitoring; 30.5% were replaced by hearing aids; 29.4% were fitted with hearing aids; 8.4% ear mold issues and 4.0% needed medical report. CONCLUSION: The age of the hearing aid made it possible to differentiate the type of team needed on the day of the appointment and the information on the date of the last audiometry and the age of the hearing aid were the information that proved to be useful in determining the type of appointment